2020
DOI: 10.3174/ajnr.a6743
|View full text |Cite
|
Sign up to set email alerts
|

The Perplexity Surrounding Chiari Malformations – Are We Any Wiser Now?

Abstract: Chiari malformations are a diverse group of abnormalities of the brain, craniovertebral junction, and the spine. Chiari 0, I, and 1.5 malformations, likely a spectrum of the same malformation with increasing severity, are due to the inadequacy of the para-axial mesoderm, which leads to insufficient development of occipital somites. Chiari II malformation is possibly due to nonclosure of the caudal end of the neuropore, with similar pathogenesis in the rostral end, which causes a Chiari III malformation. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Other than encephalocele, findings of Chiari II malformation are present in cases of Chiari III malformation including small posterior fossa and inferior herniation of cerebellum and brainstem. [1,4] Osseous malformations include occipital bone defects, dorsal scalloping of clivus and posterior petrous pyramids, posterior cervical agenesis, and segmentation anomalies of cervical spine. [5] Erol FS et al in 2011 reported a case of Chiari III malformation with Klippel Feil syndrome in a 4-year-old boy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than encephalocele, findings of Chiari II malformation are present in cases of Chiari III malformation including small posterior fossa and inferior herniation of cerebellum and brainstem. [1,4] Osseous malformations include occipital bone defects, dorsal scalloping of clivus and posterior petrous pyramids, posterior cervical agenesis, and segmentation anomalies of cervical spine. [5] Erol FS et al in 2011 reported a case of Chiari III malformation with Klippel Feil syndrome in a 4-year-old boy.…”
Section: Discussionmentioning
confidence: 99%
“…Other than encephalocele, findings of Chiari II malformation are present in cases of Chiari III malformation including small posterior fossa and inferior herniation of cerebellum and brainstem. [ 1 , 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…This condition has been suggested to be a fetal developmental anomaly caused both by changes in intracranial pressure during pregnancy and developmental anomalies of the calvarium and internal periosteum [24]. A current theory suggests that the CM-II and the Luckenschadel skull reflect the absence of cerebral ventricular distension because of decompression of an open neural tube [25]. Such a lack of stretching inhibits the normal development of membranous plates of the fetal calvarium, creating abnormally irregular collections of collagen fibers that, when ossified, yield the radiographic findings of the Luckenschadel skull.…”
Section: Discussionmentioning
confidence: 99%
“…A current theory suggests that the CM-II and the Luckenschadel skull reflect the absence of cerebral ventricular distension because of decompression of an open neural tube [25]. Such a lack of stretching inhibits the normal development of membranous plates of the fetal calvarium, creating abnormally irregular collections of collagen fibers that, when ossified, yield the radiographic findings of the Luckenschadel skull.…”
Section: Discussionmentioning
confidence: 99%
“…The Arnold–Chiari malformation is a congenital underdevelopment of the posterior cranial fossa that may lead to the displacement of the cerebellar tonsils in the magnum foramen, and it is divided into four types, with type 1 being the one with the minor protrusion of the cerebellar tonsils and often asymptomatic and the type 4 being the one with the major protrusion and more significant symptoms [ 1 ].…”
Section: Introductionmentioning
confidence: 99%